Entrepreneurship Learning Management Information System Supporting the Independent Campus Learning Program - Pato, Markani; Iskandar, Akbar; Amin, Syahril; Amanda, Andi Dimas Prasetyo; Dellas, Dellas (Journal of Educational Science and Technology (EST), 2024)
The study aims to: (1) identify the need to develop a learning management information system in information technology-based entrepreneurship courses in supporting the Independent Campus Learning (MBKM) program in higher education; (2) develop a learning management information system model for information technology-based entrepreneurship courses to support valid and effective MBKM in the university. The study employed a 4D model development design consisting of four stages, starting from design, development, and dissemination, and the instrument is validated using Aiken’v’s formula. The reliability is analyzed using Cronbach's alpha, and the practicality of the learning management information system is assessed using a Likert scale involving 25 students from the University of Technology Makassar Akba Makassar. It shows that the scale is very practical based on the positive responses from students and lecturers, and tests of the effectiveness of system usage. It indicated that the LMS effectively supports IT-based entrepreneurship learning, holistically improves students’ learning experience, and facilitates efficient teaching practice for lecturers. Then, the data analysis shows that the learning management information system for entrepreneurship subjects based on information technology practically supports the MBKM program.